(untitled) (Journal of Management and Business Education, 2020)
The investment in training and the improvement in the professional’s abilities should anticipate an evolution in the professional’s performance, but how could we estimate the probability of performance improvement from a formative action? The present work tries to quantify this using a study on 447 surveys carried out by Overlap consultant firm to professionals of the sales force of one of its clients. With this information, an artificial intelligence model has been trained. This model quantifies the relationship between skills and training on the performance of the professional and allows to measure how the probability of a better performance would increase after a training course or improvement capacity. Thus, the artificial intelligence model can be used to define the optimal profile of the professional that should carry out this activity, a profile to seek in the selection processes and in the planning of the company’s internal training.